PENGARUH PENGGUNAAN MODEL EXAMPLES NON EXAMPLES TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SDN SIAYUH KECAMATAN KELUMPANG BARAT KABUPATEN KOTABARU - Rudy Suryana (STKIP Paris Barantai, 2017)
The learning of writing skills at the elementary level is the basis for the higher level later but in general writing skills in elementary school students is still low for it need special learning for students to increase their writing skills, one of the learning models for it can be used model examples non examples, for that from this research is known influence of usage of model examples non examplesterhadap skill writing skill of narration at student of class V SDN Siayuh Kecamatan Kelumpang Barat Regency Kotabaru. This research is in the form of class research because it cooperates with classroom teacher to conduct research activities in class by comparing between learning model of lecture with model examples non examples. The results showed that the application of examples non examples model in the process of writing narrative writing can improve the students' writing skill from the previous grade average score of 60 to 88.58 or an increase of 38.43% so that this model is very effective used by teachers Indonesian and Indonesian Literature if they have problems writing skills to their students. Keywords: Writing Skill, Model Examples Non Examples